Electron beam cross-linking of NR/LLDPE blends - Ahmad A.; Mohd D.Hj.; Abdullah I. (2023)
Effects of electron beam irradiation on the mechanical properties and morphological structure of natural rubber (NR)/linear-low density polyethylene (LLDPE) blend was investigated. The NR/LLDPE blend was prepared by melt blending in a Haake internal mixer at 140C, rotor speed of 50 rpm, and in 15 min. Liquid natural rubber (LNR) was incorporated into the blend as a compatibilizer. Samples in the form of 1 mm sheets were exposed to 50-300 kGy of electron beam irradiation and analyzed for swelling index and gel content, tensile strength, and surface morphology. The result indicated that gel content and mechanical properties of the samples increased with radiation dosage. The honey-comb structure of the surface morphology in low dosage irradiated samples slowly transformed into a continuous matrix on increasing radiation dose. The variation of mechanical and physical properties was due to increase in cross-linking density in the rubber and plastic phases and rubber-plastic interaction on irradiation.